Metacarpal trabecular bone varies with distinct hand‐positions used in hominid locomotion. Issue 1 (17th May 2019) - Dunmore, Christopher J.; Kivell, Tracy L.; Bardo, Ameline; Skinner, Matthew M.
Abstract: Trabecular bone remodels during life in response to loading and thus should, at least in part, reflect potential variation in the magnitude, frequency and direction of joint loading across different hominid species. Here we analyse the trabecular structure across all non‐pollical metacarpal distal heads (Mc2‐5) in extant great apes, expanding on previous volume of interest and whole‐epiphysis analyses that have largely focused on only the first or third metacarpal. Specifically, we employ both a univariate statistical mapping and a multivariate approach to test for both inter‐ray and interspecific differences in relative trabecular bone volume fraction (RBV/TV) and degree of anisotropy (DA) in Mc2‐5 subchondral trabecular bone. Results demonstrate that whereas DA values only separate Pongo from African apes ( Pan troglodytes, Pan paniscus, Gorilla gorilla ), RBV/TV distribution varies with the predicted loading of the metacarpophalangeal (McP) joints during locomotor behaviours in each species. Gorilla exhibits a relatively dorsal distribution of RBV/TV consistent with habitual hyper‐extension of the McP joints during knuckle‐walking, whereas Pongo has a palmar distribution consistent with flexed McP joints used to grasp arboreal substrates. Both Pan species possess a disto‐dorsal distribution of RBV/TV, compatible with multiple hand postures associated with a more varied locomotor regime. Further inter‐ray comparisons reveal RBV/TV patterns consistent with varied knuckle‐walking postures in Pan species in contrast to higher RBV/TV values toward the midline of the hand in Mc2 and Mc5 of Gorilla, consistent with habitual palm‐back knuckle‐walking. These patterns of trabecular bone distribution and structure reflect different behavioural signals that could be useful for determining the behaviours of fossil hominins.